HUJAN PRESFEKTIF AL-QURAN DAN SAINS - Rika Summalia; Efendi Efendi; Faizin Faizin (UIN Imam Bonjol Padang, 2023)
Rain is understood sometimes hagoslot as grace and also as doom. Whereas The rain, when viewed from the process of falling, has the same understanding, namely: because of natural processes alone. Rain is one of the many natural phenomena that occur in human life that are mentioned in the Quran and even many studies and scientists have studied this. But this study will try to decipher the process of rain. This research uses library research, which is research that uses library study methods to collect data, review various literature and analyze topics relevant to research by browsing the literature by utilizing sources in the form of books, journals, dictionaries, documents, magazines and other sources related to research. The results of this study are expected to provide an explanation of the process of rain perspective of the Quran and science. (1) Rain in the Qur'an is expressed in four terms: maṭar, ghayth, anzala, māa, and wadqu. Water rain according to the Qur'an is water that falls is mercy, that is, it will revive the dead soil and support the plants. (2) The process of rain falling according to the Qur'an is the same as the process of raining rain in science. Rain is the result of the water cycle process, that is, starting with seawater, lakes, and rivers evaporating due to being heated by sunlight and then after reaching the top there is a condensation process so that it becomes grains of water vapor in the clouds. For this reason, the concept of rain according to the Qur'an is relevant to environmental conservation, because the cycle depends on natural conditions.